2019
DOI: 10.1371/journal.pone.0212271
|View full text |Cite
|
Sign up to set email alerts
|

“I am still negative”: Female sex workers’ perspectives on uptake and use of daily pre-exposure prophylaxis for HIV prevention in South Africa

Abstract: Women remain highly vulnerable to HIV infection in sub-Saharan Africa, with female sex workers (FSWs) facing some of the highest rates of HIV. Oral pre-exposure prophylaxis (PrEP) has the potential to reduce new infections among populations at highest risk and end-user perspectives of actual use in ‘real-world’ settings are critical to informing PrEP implementation. This paper presents findings from serial in-depth interviews (IDIs) conducted with FSW participants during the course of the Treatment And Prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 43 publications
7
39
0
Order By: Relevance
“…Quantitative analyses among men who have sex with men (MSM) in the United States and Africa and heterosexual women in the United States have found that stigma significantly reduces PrEP interest, uptake and adherence [14,[22][23][24][25][26][27][28]. Stigma may also influence African women's PrEP adherence as shown by qualitative work conducted among AGYW and FSWs that describes women's need to discreetly use HIV prevention products and miss doses because of concerns around stigma [18,19,[27][28][29][30].…”
mentioning
confidence: 99%
“…Quantitative analyses among men who have sex with men (MSM) in the United States and Africa and heterosexual women in the United States have found that stigma significantly reduces PrEP interest, uptake and adherence [14,[22][23][24][25][26][27][28]. Stigma may also influence African women's PrEP adherence as shown by qualitative work conducted among AGYW and FSWs that describes women's need to discreetly use HIV prevention products and miss doses because of concerns around stigma [18,19,[27][28][29][30].…”
mentioning
confidence: 99%
“…The potential for individuals on PrEP to reduce their use of condoms due to negation of HIV risk is a commonly voiced concern . Nonetheless, acceptability studies suggest that FSWs consider PrEP a favourable user‐controlled back‐up option for when condoms fail or cannot be used, rather than an alternative . Based on a recent meta‐analysis, individuals starting PrEP have a high burden of STIs .…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy and childcare may also lead to women taking unplanned or unwanted breaks from sex work, thus adding to household insecurity . Conversely, for some FSWs, responsibility to care for children may be a motivator to use PrEP in order to stay healthy and maintain their earning potential .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PrEP demonstration before its roll out could be critcical for the success of the program. The first demonstration study in South Africa reported that not having faith in efficacy of PrEP affected retention and adherence (32). Several side effects which were the symptoms of Reproductive Tract Infections (RTIs) were openly associated with any medical product being used by them.…”
Section: 2) Preserving Beauty / Female Physical Attributes: Concernmentioning
confidence: 99%